THEORETICAL AND EXPERIMENTAL STUDY OF THE CRACK FORMATION DEVICE IN THE SHELL OF APRICOT KERNELS - Djuraev, Khairullo; Urinov, Sherali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article conducts research on the analysis of kinetic patterns of crack formation on the shell of apricot kernels. The analysis of various devices for processing fruit kernels is presented, as well as their disadvantages and advantages. Patent data and research works of scientists from far and near abroad on the formation of cracks on the shell and splitting of fruit kernels have been studied. Accordingly, a description of a technological device designed for splitting apricot kernels, operating in continuous operation, is given. On the basis of theoretical and experimental studies, the geometric characteristics of the kernels of various apricot fruits were analyzed and the description of the forces acting on the splitting process was given, as well as the geometric parameters of apricot kernels were studied. The developed device, based on theoretical and experimental studies, ensures the formation of a small crack in the shell of an apricot kernels, and also contributes to 85-87% of the integrity of the core when splitting in a continuous process.